Isolate((R)) and Optiprep((R)) minigradients as alternatives for sperm selection in bovine in vitro embryo production - Vianna, L. L.; Pradiee, J.; Santos, E. C. S.; Goncalves, A. O.; Pfeifer, L. F. M.; Rheingantz, M. G. T.; Dode, M. A. N.; Vieira, A. D.; Lima, V. F. H. [UNESP]; Correa, M. N.; Pegoraro, L. M. C. (Agricultural Inst Canada, 2014)
The objective of this study was to evaluate alternatives in small volumes to conventional gradient of Percoll((R)) on semen quality, in vitro embryo production, sex ratio and embryo survival after vitrification. Thawed semen was randomly allocated to one of four density gradient selection methods: (1) conventional Percoll((R)) (P), (2) MiniPercoll (MP), (3) MiniIsolate (MI), and (4) MiniOptiprep (MO). Sperm kinetics and quality were evaluated. Use of P, MP and MI gradients did not affect sperm motility (P > 0.05). However, there was a decrease in total and progressive sperm motility in MO (70.8 and 51.3% vs. 87.3 and 69.5% for P; 87.3 and 73% for MP; 92.3 and 78.8% for MI; P < 0.05). The MO had lower membrane integrity compared with P, MP and MI (39.7 vs. 70.5, 72.3, 63.8%, respectively, P < 0.05). The percentage of blastocysts produced was higher in MI than in MP and MO (21.1 vs. 16.1 and 16.9%, P < 0.05) and similar to P (18.4%; P > 0.05). Sex ratio and embryo survival after vitrification were similar among groups (P > 0.05). Semen selected by Isolate and Optiprep gradient, at the concentrations and small volumes used, demonstrated similar characteristics and in vitro embryo production to conventional Percoll((R)) gradient.
Keywords: In vitro fertilization; sperm selection; sex ratio; sperm quality; cryopreservation